Qualitative research on sport and physical culture - Young, Kevin, 1959-; Atkinson, Michael, 1971- (Bingley, U.K. : Emerald, 2012)
This volume takes a fresh approach to qualitative research on sport and physical culture by presenting "student friendly" engaging chapters that clearly articulate the significance and practice of qualitative and/or critical methods in plain and convincing language. It outlines contemporary, cutting-edge approaches in qualitative research methods that students in undergraduate programs in sociology and sociology of sport, as well as, for instance, sport, exercise, kinesiology, or health, can understand clearly. Chapters revolve around one principal method in qualitative methodology, and look at why certain methodological choices were made, what problems were faced, and how these were overcome. Classic issues in methodology, contemporary issues in research methods and innovative trends in qualitative research are addressed through case study examples from emerging and exciting areas of research in sport studies. Topics covered include: historical methods; ethnography; auto-ethnography; embodied methods; interviewing; narratives; participatory action methods; interpretative phenomenological analysis; media analysis; and visual methods.
Introduction : the practice of qualitative research and thinking qualitatively / Kevin Young, Michael Atkinson -- ch. 1. Historical methods and traces of the past : embracing the complexities and engaging in reflexivity / Carly Adams -- ch. 2. The empirical strikes back : doing realist ethnography / Michael Atkinson -- ch. 3. The ethnographic (I)nterview in the sports field : towards a postmodern sensibility / Holly Thorpe -- ch. 4. Narrative analysis in sport and physical culture / Brett Smith, Andrew C. Sparkes -- ch. 5. Visual methods in physical culture : body culture exhibition / Emma Rich, Kerrie O'Connell -- ch. 6. Media analysis in physical cultural studies : from production to reception / Brad Millington, Brian Wilson -- ch. 7. Critical feminist/queer methodologies : deconstructing (hetero)normative inscriptions / Caroline Fusco -- ch. 8. Embodied research methodologies and seeking the senses in sport and physical culture : a fleshing out of problems and possibilities / Andrew C. Sparkes, Brett Smith -- ch. 9. Autoethnography : situating personal sporting narratives in socio-cultural contexts / Jacquelyn Allen-Collinson -- ch. 10. Two (or more) feet are better than one : mixed methods research in sport and physical culture / Kass Gibson -- ch. 11. Truth or dare : examining the perils, pains and pitfalls of investigative methodologies in the sociology of sport / John Sugden.
Keywords: Sports & Recreation -- Sociology of Sports; Social Science -- Sociology -- General; Social Science -- General; Sociology: sport & leisure; Society & culture: general; Sports -- Research; Sports -- Research -- Methodology